1996
DOI: 10.5694/j.1326-5377.1996.tb122121.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential continuity of care by general practitioners: which patients change doctor?

Abstract: Objective: To identify individual and social characteristics of patients making sequential visits to a different rather than the same general practitioner (GP). was treated as an event.Participants: 521 subjects aged between 23 and 72 years who gave consent to release of Health Insurance Commission data.Main outcome measure: A visit to the same GP or a different GP from the one seen at the last visit.Results: Logistic regression analysis showed that younger age, good physical functioning, good self-rated healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…One article15 was published in 1996 and 10 articles were published after 2000. The studies were carried out in Canada, UK, Australia and Taiwan.…”
Section: Resultsmentioning
confidence: 99%
“…One article15 was published in 1996 and 10 articles were published after 2000. The studies were carried out in Canada, UK, Australia and Taiwan.…”
Section: Resultsmentioning
confidence: 99%
“…A recently published report from the Canadian Health Services Foundation has addressed the confusion regarding the definition of continuity of care. 146 One [30][31][32]34,[36][37][38][39][40] Christakis et al, 1999 118 Flynn, 1985 45 Roos et al, 1980 36 Sloane & Eglehoff, 1983 75 Wasson et al, 1984 66 Number of Providers Seen Raddish et al, 1999 117 (NOP) 20 Shortell et al, 1977 49 Sequential Continuity Index Phillips & Shear, 1984 88 (SECON) 20,34,37,38,40 Pilotto et al, 1996 73 Shear et al, 1983 64 Wasson et al, 1984 66 Likelihood of Continuity Index (LICON) 20,34,38 Likelihood of Sequential Continuity Index (LISECON) 20,38 Herfindahl Index (HH) 20,39 Modified Continuity Index Gill & Mainous, 1998 90 (MCI) 31,37 Gill et al, 2000 115 Neher et al, 2001 124 Sturmberg & Schattner, 2001 100 Modified, Modified Continuity Gill & Mainous, 1998 90 Index (MMCI) 31 Gill et al, 2000 115 Neher et al, 2001 124 Index of Concentration (CON) 22,38 GINI Index of Concentration (GINI)…”
Section: Discussionmentioning
confidence: 99%
“…However, it might be conjectured that the small, but constant, proportion of provider transience by GPs may have had a ripple effect on access in the ACT. One study in New Zealand has shown that the size of a general practice was influenced by word of mouth [17,18]. Parents might report on their experience of transient GPs to other parents who might then choose not to nominate that practice for their child.…”
Section: Discussionmentioning
confidence: 99%